2017
DOI: 10.1080/02626667.2016.1260134
|View full text |Cite
|
Sign up to set email alerts
|

Generalized extreme value shape parameter and its nature for extreme precipitation using long time series and the Bayesian approach

Abstract: Assessing the probability of extreme precipitation events is consequential in civil planning. This requires an understanding of how return values change with return periods, which is essentially described by the generalized extreme value (GEV) shape parameter. Some works in the field suggest a constant shape parameter, while our analysis indicates a non-universal value. We reanalysed an older precipitation dataset (169 stations) extended by Norwegian data (71 stations). We showed that while each set seems to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…The 3SP systematically displayed higher shape values than 7SP, with positive median ξ t values distributed around ξ t ≈ 0.17. This result is consistent with typical GEV shape parameter values estimated from long records (e.g., more than 100 years) and reported in the literature (e.g., Ragulina & Reitan, 2017, and references therein). For instance Koutsoyiannis (2004a) and Koutsoyiannis (2004b) reported positive ξ values lower than ≈0.23 for various locations around the world.…”
Section: Projected Changes In Am Probability Distributionssupporting
confidence: 92%
See 1 more Smart Citation
“…The 3SP systematically displayed higher shape values than 7SP, with positive median ξ t values distributed around ξ t ≈ 0.17. This result is consistent with typical GEV shape parameter values estimated from long records (e.g., more than 100 years) and reported in the literature (e.g., Ragulina & Reitan, 2017, and references therein). For instance Koutsoyiannis (2004a) and Koutsoyiannis (2004b) reported positive ξ values lower than ≈0.23 for various locations around the world.…”
Section: Projected Changes In Am Probability Distributionssupporting
confidence: 92%
“…Third, SD shape parameter values were larger than corresponding LD values for each 3SP for more than 61% of the grid boxes, as also shown by the SD and LD ξ Ã t;r distributions (Figure 11b; note that only significant ξ Ã t;r >0 are considered in this figure). Accordingly, SD extremes displayed heavier tailed distributions than longer-duration AM, which is consistent with the hypothesis that links the shape parameter values to the characteristic precipitation systems generating AM at different temporal scales (Ragulina & Reitan, 2017).…”
Section: Projected Changes In the Spatiotemporal Structure Of Am Precsupporting
confidence: 88%
“…The estimation of κ is notoriously difficult due to its sensitivity to record length (Overeem et al 2008, Papalexiou and Koutsoyiannis 2013, Ragulina and Reitan 2017. Indeed, it has been demonstrated that for sample sizes less than 50, using a two parameter Gumbel distribution results in a smaller error than the three parameter GEV (Lu and Stedinger 1992).…”
Section: Estimation Of Distribution Parametersmentioning
confidence: 99%
“…where, τ, α, and k represents location, scale and shape parameters of the distribution function. GEV like other probability distributions is affected by short hydrological time series, which results in uncertain flood estimates [85], therefore the availability of more historical data enables improved flood estimation. The 5T rule of thumb suggested by Reed [78] for the length of data required for flood frequency estimation is adopted for this study, i.e., the historical data should be at least five times the target return periods (i.e., 20 years of historical data is required for a 1-in-100-year estimation, for reasonable levels of uncertainty).…”
Section: Flood Frequency Estimationmentioning
confidence: 99%